Exchange Rates, Gold and Money Demand in India and South Africa - Seyyedi, Seyyedsajjad (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
This dissertation endeavors to explore the different aspects of macroeconomic factors such as the exchange rate, price of gold and demand function for money in India and South Africa respectively. In the second chapter, we investigate the co-movements and relationships among gold and oil prices and Indian Rupee (INR) to US Dollar (USD) exchange rate over the period of January 12, 2004 to April 30, 2015, to consider whether economic policymakers in India should separate financial policies and energy policies. We use different econometric methods such as Johansen’s cointegration test, vector autoregressive (VAR) model, Granger-causality test and impulse response to describe the relationships among the factors. Our empirical results show that in spite of short-run causality effects between the variables, there is not a long-run relationship between them. This analysis provides a number of important economic insight into these markets in India. The third chapter is an empirical exercise in money demand behavior, testing whether economic and monetary uncertainties may affect the demand function for money in South Africa. This is often done by utilizing the unlimited error-correction model and bounds testing method to cointegration explained by Pesaran et al. (2001). We employ the moving-average standard deviation method to generate the results uncertainty estimation and monetary uncertainty estimation. The results suggest that any increase in output uncertainty causes a substitution effect away from cash and less volatile assets, whereas an increase in monetary uncertainty causes a precautionary impact to save more volatile assets i.e. cash. Finally, we use Brown et al.’s (1975) cumulative sum (CUSUM) and cumulative sum of squares (CUSUMSQ) tests to consider the coefficients strength. Our findings report the steady demand function for money in South Africa. In the fourth chapter, we check the impact of domestic and foreign interest rate volatility on the demand function for money in South Africa. Our findings show that the measure of interest rate volatility on domestic money has a negative relationship with the demand for money. This could induce a few investors to move a portion of their wealth out of ostensible resources, including money, into substantial resources such as product inventories. Moreover, the foreign interest rate fluctuation measure is not significantly related to the demand function for money in South Africa. The findings imply that monetary and financial policies have an important role in explaining the economy of less developed countries. Keywords: Exchange rate, gold price, oil price, money demand, India, South Africa.

ÖZ:Bu tez Hindistan ve Güney Afrika'daki döviz kurları, altın fiyatları ve para talebi fonksiyonu gibi makroekonomik değişkenlerin farklı yönlerini keşfetmeye çalışmaktadır. Birinci bölümde, Hintli ekonomik politika belirleyicilerinin finansal politikaları enerji politikalarından ayırmalarının gerekip gerekmediğini araştırmak için 12 Ocak 2004 - 30 Nisan 2015 tarihleri arasındaki altın fiyatları, petrol fiyatları ve Hindistan Rupisi-dolar döviz kurları arasındaki ortak hareketleri ve bağlantıları araştırıyoruz. Değişkenler arasındaki eş hareketleri açıklamak için Johansen’in eşbütünleşme testi, vektör otoregresif (VAR) modeli, Granger nedensellik testi ve dürtü yanıtı gibi çeşitli ekonometrik yöntemler kullanılmıştır. Bu bağlamda, altın fiyatlarının, petrol fiyatlarının ve rupi-dolar döviz kurlarının birbirinden büyük ölçüde bağımsız olduğu ve dolayısıyla enerji politikalarının ve finansal politikaların birbirinden ayrı düşünülmesi sonucuna varılmıştır. İkinci bölüm, ekonomik ve parasal belirsizliklerin Güney Afrika'daki para talebi işlevini etkileyip etkilemediğini test eden ampirik bir çalışrmadır. Bu çalışmada, sınırsız hata düzeltme modeli ve Pesaran ve arkadaşlarının (2001) önerdiği eşbütünleşme için sınır testi yaklaşımı kullanıldı. Çıktı belirsizlik ölçüsü ve parasal belirsizlik ölçüsü oluşturmak için hareketli ortalama standart sapma yöntemini kullanıyoruz. Sonuçlar, çıktı belirsizliğindeki herhangi bir artışın, nakitten uzak ve daha az değişken varlıklar lehine bir ikame etkisine yol açtığını, parasal belirsizliğin artmasından dolayı, daha fazla değişkenlikten tasarruf etmenin bir ihtiyati etki olduğunu göstermektedir. Son olarak, Brown ve arkadaşlarının (1975) kümülatif toplamı (CUSUM) ve kümülatif kareler toplamı (CUSUMSQ) testlerini, katsayıların durağanlığını değerlendirmek için kullandık. Bulgularımız Güney Afrika'da para talebi fonksiyonunun istikrarlı olduğunu gösteriyor. Son bölümde, Güney Afrika'daki yerli ve yabancı faiz oranındaki dalgalanmaların para talebi fonksiyonu üzerindeki etkilerini kontrol ettik. Bulgularımız, faiz oranının yerel para üzerindeki hareketliliğinin para talebiyle olumsuz yönde ilişkili olduğunu göstermektedir. Bu, bazı yatırımcıların servetlerinin bir kısmını nominal varlıklardan emtia stokları gibi maddi varlıklara kaydırmaya zorlayabilir. Öte yandan, yabancı faiz oranı hareketliliğinin, Güney Afrika'daki para talebi fonksiyonu ile önemli bir ilişkisi yoktur. Bu sonuçlar, parasal ve finansal politikaların, gelişmekte olan ülkelerin ekonomisini açıklamada önemli bir rol oynadığını göstermektedir. Anahtar Kelimeler: Döviz kuru, altın fiyatı, petrol fiyatı, para talebi, Hindistan.
Doctor of Philosophy in Economics. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2019. Supervisor: Prof. Dr. Glenn Paul Jenkins.
Keywords: Money-Economics-India-Asouth Africa; Exchange rate; gold price; oil price; money demand; India; South Africa; Economics